eHealth Connect. Mobile Appointment and Health Record System - Achouak, Debbache; Hadil, Belhadi (University of M'sila, 2026)
Contemporary healthcare systems are undergoing digital transformation to overcome the lim itations of traditional paper-based methods. In this context, this project presents "Nibras es iha", an integrated digital platform connecting six key actors within the healthcare ecosystem: patient, doctor, medical assistant, pharmacist, laboratory, and administrator. The system was developed following a three-tier monolithic architecture. The backend was built using PHP with a MySQL database, while the Android application was developed in Java. Communication between components is ensured through a REST API using JSON format. The platform features a smart appointment booking mechanism that prioritizes re turning patients, supports electronic prescription transmission to pharmacies and test requests to laboratories, and provides real-time notifications both in-app and via SMS using a GSM modem. It also offers role-specific dashboards, subscription management (15-day free trial followed by monthly/yearly plans), advanced analytics, and secure chat functionality. The system was functionally tested on a Pixel 3 emulator running Android 13 (API 33) and demonstrated promising results. This project contributes to the digitalization of small clinics at low cost and provides a foundation for future enhancements such as artificial intel ligence and telemedicine.
Keywords: Digital health; health information system; smart appointment booking; electronic prescriptions